THE RESULTS OF A PHASE III COMPARATIVE CLINICAL TRIAL OF RITUXIMAB (ACELLBIA® AND MABTHERA®) IN RHEUMATOID ARTHRITIS (THE BIORA STUDY) - E. L. Nasonov; E. V. Zonova; O. N. Ivanova; L. A. Knyazeva; V. I. Mazurov; R. R. Samigullina; I. M. Marusenko; O. B. Nesmeyanova; T. V. Plaksina; A. E. Sizikov; D. G. Krechikova; N. A. Petrochenkova; et al. (Научно-практическая ревматология)
The article considers the results of an international multicenter randomized clinical trial of the efficacy and safety of the brand-name drug rituximab (MabThera), a monoclonal antibody against CD20 antigen of B cells, and its biosimi-lar drug (Acellbia®) (the BIORA study) in patients with rheumatoid arthritis (RA) refractory to therapy with tumor necrosis factor-а inhibitors.Objective: to provide evidence for the therapeutic equivalence of Acellbia® and MabThera® and also to assess their interchangeability.Subjects and methods. The trial enrolled adult patients with active seropositive RA, who were randomized into two groups (1:1): 1) the patients who received Acellbia® 1000 mg intravenously on days 1 and 15; 2) those who had MabThera® in a similar way. When RA activity persisted at 24 weeks, there was re-randomization (1:1) with a partial overlap: Group 1 patients were randomized into group AA (the drug of the second therapy cycle was Acellbia®) or Group AM (that was MabThera®), the similar methodology was followed in Group 2 (Groups MM and MA). Throughout the study, the patients received methotrexate at a stable dose of 7.5—25 mg/week and folic acid at a dose of 5 mg/week. The follow-up lasted 48 weeks.Results and discussion. 24 weeks after treatment initiation, the ACR20 response was observed in 84.1% of the patients in the Acellbia® group (95% CI, 74.75—90.50) and in 87% in the MabThera® group (95% CI, 77.71—92.79%; p = 0.773), which suggests that the drugs are therapeutically equivalent. In the second phase of the study, the efficiency of therapy remained high; there were no differences in Groups AA/MM, AA/AM and MM/MA. In both phases, the safety profile of the drugs was comparable; the immunogenicity of treatment remained low. The findings suggest that the brand-name MabThera® and its biosimilar drug Acellbia® are equivalent. Switching from the biosimilar drug to the brand-name one and vice versa has no negative impact on treatment outcomes.